2018
DOI: 10.7150/jca.24980
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MET copy number gain in non-small-cell lung cancer: an updated meta-analysis

Abstract: The alterations of MET have been detected in non-small-cell lung cancer (NSCLC). However, the prognostic impact of MET gene copy number gain (CNG) has not been consistent among studies. We performed this meta-analysis to evaluate the prognostic value of high MET CNG in patients with NSCLC. A systematic computerized search of the electronic databases including PubMed, EMBASE, Google scholar, and Cochrane Library (up to November 2017) was carried out. From twenty-one studies, 7,647 patients were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…There are a few meta-analyses in the literature on the prognostic role of MET CNG in NSCLC [64,67,118]. A recent meta-analysis combined the results from 21 studies that involved 7647 patients and showed the association between MET CNG and inferior OS (HR 1.45, 95% CI 1.16-1.80) [64].…”
Section: Ii-b-met Gene Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few meta-analyses in the literature on the prognostic role of MET CNG in NSCLC [64,67,118]. A recent meta-analysis combined the results from 21 studies that involved 7647 patients and showed the association between MET CNG and inferior OS (HR 1.45, 95% CI 1.16-1.80) [64].…”
Section: Ii-b-met Gene Amplificationmentioning
confidence: 99%
“…There are a few meta-analyses in the literature on the prognostic role of MET CNG in NSCLC [64,67,118]. A recent meta-analysis combined the results from 21 studies that involved 7647 patients and showed the association between MET CNG and inferior OS (HR 1.45, 95% CI 1.16-1.80) [64]. Subgroup analyses based on histology and ethnicity indicated that MET CNG significantly correlated with shorter survival, especially in patients with adenocarcinoma (HR 1.41, 95% CI 1.11-1.79) and in Asian populations (HR 1.58, 95% CI 1.32-1.88).…”
Section: Ii-b-met Gene Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations on transcription level of MET gene, which includes MET amplification and MET exon 14 skipping mutation could be the potential mechanisms (21). Additionally, high gene copy number (GCN) of MET was also found be an adverse survival indicator in several studies (59)(60)(61). Nevertheless, MET positivity was notably higher, with a prevalence ranged up-till 70% among NSCLC, compared with MET mutations (around 4%) (58).…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of METex14 mutations was 1.7-4.3% in metastatic lung adenocarcinomas, according to NGS analyses. [46][47][48]55,58 METex14-skipping mutations tend to be more frequent in relatively elderly populations and mutually exclusive of other lung cancer-driver mutations. 71,72 METex14-skipping mutations have been identified across different major histological subtypes of lung cancers, eg adenosquamous (8.2%) or sarcomatoid subtypes (7.7%), adenocarcinomas (2.9%) and squamous-cell carcinomas (2.1%).…”
Section: Mutationsmentioning
confidence: 99%